Exploration of cinema architecture to resurge cinema as a cultural laboratory in Malaysia - Gowd, Deepankursingh; Mohd Zairul (Human Resources Management Academic Research Society (HRMARS), 2024)
Malaysia is known for its plethora of cultures, traditions, and identity. Similarly, so does its cinema industry, which has existed for almost a century. The cinema theater was a place and space where people of all ages met and engaged for entertainment. As the audience keeps growing, cinema halls are moving into shopping malls where more modern and bigger halls are being built to amuse people in both shopping and entertainment, and the cinema theaters are closing down. These theaters were once an integral part of the urban fabric of the community and country. Thus, the architecture of the cinema provides a character, identity, and culture, which acts as a catalyst for a socially sustainable society. To address this, architecture and cinema are used as two integral elements of sustainability principles on the social dimension consisting of equity and social identity, aesthetics, and comfort. The study will conduct qualitative research to explore cinema architecture as a platform to promote film culture development and investigate the architectural strategies that can be incorporated into a cultural hub. Furthermore, the study will present a framework for a new cinema architecture that aims to reintroduce the cinema theater as a cinema cultural hub for the present and future generations and introduce a new perspective to the cinema theaters outside the shopping mall. In summary, the study presents research on a new approach to cinema architecture and interaction with the urban fabric and community. The research focuses on cinema theater urban shopping malls and the sustainability and criteria of cultural entertainment with the design of cinema theater and operational guidelines and mechanisms to use in cinema architecture in the urban development and community.